KU-BAND SiGe HBT I/Q SUBHARMONIC MIXER WITH REACTIVE QUADRATURE GENERATORS - Tseng, Sheng-Che; Syu, Jin-Siang; Su, Jen-Yi; Wei, Hung-Ju; Meng, Chinchun; Huang, Guo-Wei (My University, 2010)
This article demonstrates a high-frequency 0.35-mu m SiGe HBT subharmonic downconverter with reactive in-phase and quadrature-phase (I/Q) generators. Two reactive I/Q generators are integrated in our work to provide differential quadrature RF and LO signal. The I/Q subharmonic downconverter with single-ended LO. RF. and IF (I/Q) ports has a conversion gain of 1 a. IP(1dB) of -10 dBm. IIP(3) of 0 dBm, and IIP(2) of 21 dBm at 16.4 GHz. The magnitude and phase errors between the I and Q channels are 1.34% and 0.6 degrees. respectively. The dc power consumption of this IIQ mixer without output buffers is approximately 5 mW. (C) 2010 Wiley Periodicals, Inc. Microwave Opt Technol Lett 52: 1516-1520, 2010; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.25281
Keywords: direct conversion; IIQ; SiGe HBT; subharmonic; transformer